The 2001 Cape Town Convention on International Interests in Mobile Equipment/the Aviation Protocol and Relevant issues in Indonesian Aviation Law - Kantaatmadja, Mieke Komar (UI Scholars Hub, 2021)
The 2001 Cape Town Convention provides a mechanism for recognizing and recording international security interest in high- value moveable equipment. However, Law No.83 of 1958 did not mention the recording of secured private rights or security interests in aircrafts. Furthermore, Law No.15 of 1992 on Airport Transportation succeeded Law No.83 of 1958 which contained some rules on secured rights in aircraft. Chapter X of the new law no 1 of 2009 on Aviation could be regarded as the implementation of the Ratified Cape Town Convention and its Protocol. Does it mean that a national interest should be registered in the International registry, even though the aircraft object is legally owned by an Indonesian seller /lessor/creditor, but beneficially owned and operated by an Indonesian airliner/lessee based on a contract governed by Indonesian Law?